Regulation of Osteoclast Growth and Fusion by mTOR/raptor and mTOR/rictor/Akt - Tiedemann, Kerstin; Le Nihouannen, Damien; Fong, Jenna E.; Hussein, Osama; Barralet, Jake E.; Komarova, Svetlana V. (Frontiers in Cell and Developmental Biology, 2017)
Osteoclasts are giant bone cells formed by fusion from monocytes and uniquely capable of a complete destruction of mineralized tissues. Previously, we have demonstrated that in energy-rich environment not only osteoclast fusion index (the number of nuclei each osteoclast contains), but also cytoplasm volume per single nucleus was increased. The goal of this study was to investigate the regulation of metabolic sensor mTOR during osteoclast differentiation in energy-rich environment simulated by addition of pyruvate. We have found that in the presence of pyruvate, the proportion of mTOR associated with raptor increased, while mTOR-rictor-mediated Akt phosphorylation decreased. Inhibition of mTOR with rapamycin (10 nM) significantly interfered with all aspects of osteoclastogenesis. However rapamycin at 1 nM, which preferentially targets mTOR-raptor complex, was only effective in control cultures, while in the presence of pyruvate osteoclast fusion index was successfully increased. Inhibition of Akt drastically reduced osteoclast fusion, however in energy-rich environment, osteoclasts of comparable size were formed through increased cytoplasm growth. These data suggest that mTOR-rictor mediated Akt signaling controls osteoclast fusion, while mTOR-raptor regulation of protein translation contributes to fusion-independent cytoplasm growth. We demonstrate that depending on the bioenergetics microenvironment osteoclastogenesis can adjust to occur through preferential multinucleation or through cell growth, implying that attaining large cell size is part of the osteoclast differentiation program.